1. wykonaj działania
a) [tex]\frac{4}{x-1}[/tex]-[tex]\frac{4x-1}{x+2}[/tex]
b) [tex]\frac{x-1}{x-4}[/tex]+4
c)[tex]\frac{x^{2}-2x }{9-x^{2} }[/tex]:[tex]\frac{x-2}{3-x}[/tex]


Odpowiedź :

Odpowiedź:

a)                 x-1≠0       x+2≠0           D=R\{ -2,1}

[ 4(x+2)-(4x-1)(x-1)]/(x-1)(x+2)=

( 4x+8-4x²+4x+x-1)/( x²+x-2)=(-4x²+9x+7)/(x²+x-2)

b)

x-4≠0           D=R\{4}

[x-1+4(x-4)] /(x-4)= ( x-1+4x-16)/(x-4)=( 5x-17)/(x-4)

c)

9-x²≠0             x-2≠0            3-x≠0         D=R\{ -3,3,2}

x(x-2) / (3-x)(3+x)  * (3-x) /(x-2)=x/(3+x)

Szczegółowe wyjaśnienie: